2021
DOI: 10.1016/j.jbc.2021.100902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinical isolate or cleavage site mutations in the SARS-CoV-2 spike protein on protein stability, cleavage, and cell–cell fusion

Abstract: The trimeric SARS-CoV-2 spike protein (S) is the sole viral protein responsible for both viral binding to a host cell and the membrane fusion event needed for cell entry. In addition to facilitating fusion needed for viral entry, S can also drive cell-cell fusion, a pathogenic effect observed in the lungs of SARS-CoV-2 infected patients. While several studies have investigated S requirements involved in viral particle entry, examination of S stability and factors involved in S cell-cell fusion remain limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…There have been a plethora of structural studies, both physical and computational, carried out on the SARS-CoV-2 spike protein since its discovery in December 2019. ,,, While this has allowed the binding of the spike protein to the host cell receptor, ACE2, to be investigated extensively, the molecular mechanisms behind membrane fusion remain elusive. Imperative in this pursuit is the elucidation of the spike protein while associated with a lipid membrane; however, this poses its own challenges.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a plethora of structural studies, both physical and computational, carried out on the SARS-CoV-2 spike protein since its discovery in December 2019. ,,, While this has allowed the binding of the spike protein to the host cell receptor, ACE2, to be investigated extensively, the molecular mechanisms behind membrane fusion remain elusive. Imperative in this pursuit is the elucidation of the spike protein while associated with a lipid membrane; however, this poses its own challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike SARS-CoV-2 α variant, 9 mutation sites of SARS-CoV-2 β variant are detected in subunit (S) 1 region, where the enzyme cleaves between N-terminal S1 (14–685 amino acid residues) region and C-terminal S2 (686–1,213 amino acid residues) region of spike extracellular protein ( Fig. 1B ) prior to SARS-CoV-2 entering a host cell ( 41 42 43 44 ). A single point mutation A701V presents in the S2 region that is distinct from SARS-CoV-2 α variant.…”
Section: Sars-cov-2 β (B1351) Variantmentioning
confidence: 99%
“…We and others had previously shown that the S protein interacting with the ACE2 receptor induces cell–cell fusion (Buchrieser et␣al , 2020 ; Braga et␣al , 2021 ; Lin et␣al , 2021 ; Sanders et␣al , 2021 ; Zhang et␣al , 2021 ). The TMPRSS2 protease further augments cell–cell fusion (Buchrieser et␣al , 2020 ; Barrett et␣al , 2021 ; Hornich et␣al , 2021 ).…”
Section: Introductionmentioning
confidence: 99%